Role of anuria in the relationship between indoxyl sulfate and anemia in peritoneal dialysis patients - Huang JY; Hsu CW; Yang CW; Hung CC; Huang WH (Dove Medical Press, 2016)
Jeng-Yi Huang,1,2 Ching-Wei Hsu,1,2 Chih-Wei Yang,1,2 Cheng-Chieh Hung,1,2 Wen-Hung Huang1,2 1Kidney Research Center, Department of Nephrology, Chang Gung Memorial Hospital, Linkou Branch, Taipei, 2Chang Gung University School of Medicine, Taoyuan, Taiwan Background: Experimental evidence suggests that indoxyl sulfate (IS) is associated with chronic kidney disease-related anemia. However, clinical studies are limited, and few have explored the potential confounding effect of anuria. This study, thus, evaluated the association between IS and anemia in both non-anuric and anuric peritoneal dialysis (PD) patients.Methods: This cross-sectional and observational study included 165 chronic PD patients aged 19–84 years. Their serum IS levels in total and free forms were measured by ultra performance liquid chromatography. Correlations between serum IS and hemoglobin (Hb) were performed in both non-anuric and anuric groups.Results: Among the study subjects, 90 were non-anuric and 75 were anuric. As a whole, there was no correlation between IS and Hb. Nonetheless, subsequent analysis of the non-anuric patients showed that Hb is negatively correlated with IS levels (rs=-0.405, P<0.001 for total form and rs=-0.296, P=0.005 for free form). Factors that significantly affected Hb levels in the stepwise multiple regression analysis include total IS and iron saturation. In contrast for anuric patients, serum ferritin, albumin, iron saturation, use of angiotensin-converting enzyme inhibitor/angiotensin II receptor blocker, but not serum IS, were predictors for anemia in the multiple regression model.Conclusions: Serum IS is associated with an increased severity of anemia in non-anuric PD patients and not in anuric ones, indicating anuria could be a confounding factor in such association. Keywords: indoxyl sulfate, anemia, peritoneal dialysis, anuria